Justice League. The flashpoint paradox [videorecording (DVD)] - Oliva, Jay; Chambers, Justin; Howell, C. Thomas, 1966-; Jordan, Michael B. (Michael Bakari), 1987-; McKidd, Kevin; Perlman, Ron, 1950-; Fillion, Nathan, 1971-; Elwes, Cary, 1962-; Delany, Dana; Johns, Geoff, 1973-; Kubert, Andy (Warner Home Video, 2013)
The Flash gets a chance to go back in time and right a violent, decades-past crime against his mother. However, the ripples of his good intentions prove disastrous, as a fractured, alternate reality now exists in place of the familiar one. Superman is nowhere to be found, and Batman is a grittier, more violent Dark Knight. Together, with Cyborg, they race to restore the continuity of Flash's original timeline, while this new one is ravaged by war between the armies of Wonder Woman and Aquaman.